Performance Measures of Positive Output Superlift Luo Converter Using Multitudinous Controller - Sivagami Ponnalagarsamy; N. M. Jothi Swaroopan (Institute of Advanced Engineering and Science, 2018)
In order to meet the increase in energy demand globally it is necessary to harness renewable energy at its maximum potential for the purpose of electric power generation. For the achievement of high output voltage and efficiency DC-DC converters plays a vital role in low voltage PV array and fuel cells. LUO converters are gaining importance because of geometric progression output. . LUO converters find its application because of high transient performance of the system, high power transfer gain, efficiency and reduced ripple .Because of load and line disturbances the output voltage of DC-DC converter must be operated in closed loop mode. This paper interpolates multitudinous controller for positive output elementary super lift LUO converter (POESLL). The pursuance of the converter under manifold such as variation in input, load are developed and compared for current mode controller and SMC.